Identification of factors that support successful implementation of care bundles in the acute medical setting: a qualitative study. Issue 1 (December 2017) - Green, Stuart; Bell, Derek; Mays, Nicholas
Abstract Background Clinical guidelines offer an accessible synthesis of the best evidence of effectiveness of interventions, providing recommendations and standards for clinical practice. Many guidelines are relevant to the diagnosis and management of the acutely unwell patient during the first 24–48 h of admission. Care bundles are comprised of a small number of evidence-based interventions that when implemented together aim to achieve better outcomes than when implemented individually. Care bundles that are explicitly developed from guidelines to provide a set of related evidence-based actions have been shown to improve the care of many conditions in emergency, acute and critical care settings. This study aimed to review the implementation of two distinct care bundles in the acute medical setting and identify the factors that supported successful implementation. Methods Two initiatives that had used a systematic approach to quality improvement to successfully implement care bundles within the acute medical setting were selected as case studies. Contemporaneous data generated during the initiatives included the review reports, review minutes and audio recordings of the review meetings at different time points. Data were subject to deductive analysis using three domains of the Consolidated Framework for Implementation Research to identify factors that were important in the implementation of the care bundles. Results Several factors were identified that directly influenced the implementation of the care bundles. Firstly, the availability of resources to support initiatives, which included training to develop quality improvement skills within the team and building capacity within the organisation more generally. Secondly, the perceived sustainability of changes by stakeholders influenced the embedding new care processes into existing clinical systems, maximising their chance of being sustained. Thirdly, senior leadership support was seen as critical not just in supporting implementation but also in sustaining longer-term changes brought about by the initiative. Lastly, practitioner incentives were identified as potential levers to engage junior doctors, a crucial part of the acute medical work force and essential to the initiatives, as there is currently little recognition or reward for involvement Conclusions The factors identified have been shown to be supportive in the successful implementation of care bundles as a mechanism for implementing clinical guidelines. Addressing these factors at a practitioner and organisational level, alongside the use of a systematic quality improvement approach, should increase the likelihood that care bundles will be implemented successfully to deliver evidence based changes in the acute medical setting.